Capturing Online Presence: Hyperlinks and Semantic Networks in Activist Group Websites on Corporate Social Responsibility - Bakker, Frank G. A. de (Journal of business ethics, 2013)
The rise of Internet-mediated communication poses possibilities and challenges for organisation studies, also in the area of corporate social responsibility (CSR) and business and society interactions. Although social media are attracting more and more attention in this domain, websites also remain an important channel for CSR debate. In this paper, we present an explorative study of activist groups’ online presence via their websites and propose a combination of methods to study both the structural positioning of websites (hyperlink network analysis) and the meanings in these websites (semantic co-word maps). We focus on the websites of SOMO, the Centre for Research on Multinational Corporations, and of one of its campaigns, makeITfair, concerned with labour conditions in the IT industry worldwide. This allows us to show how this combination of methods can further our understanding of the way activist networks’ online presence can provide insights into the tactics these networks apply to achieve institutional change on CSR issues. Meanwhile, we identify some notable differences between styles and word use in the two organisations’ websites. We conclude with a set of suggestions for future research.